CONTROVERSIAL ASPECTS OF A CHOICE OF SYSTEM OF INFORMATION SUPPORT OF MANAGEMENT STRATEGY AND TACTICS OF DEVELOPMENT OF RAILWAY TRANSPORT - A. Bondarenko (Вестник университета)
The logical reflection of this article is based on the definition of the key positions of management tactics and development strategy of large holding companies, concepts of the digital economy as a phenomenon of understanding the goals of management. The article deals with the discussion aspects of the choice of the information support system for the management of tactics and development strategy of railway companies, identifies the causal basis of management reporting. It is concluded that the solution of strategically important and essential tasks of implementation of the program of innovative development of PJSC «RZD» requires improvement of the system of their information support, which in turn is impossible without the development of the principles and rules of accounting, management, tax accounting, as well as the formation on their basis of the principles and rules of a special system of relevant information.